Lire la Phénoménologie de l'esprit de Hegel - Bouton, Christophe; Renault, Emmanuel (La croisée des chemins, 2022)
Published in 1807, Hegel's Phenomenology of Spirit is highly original in its project, in its form and the variety of its subject-matters. It is famous notably for its "master-slave dialectics", and the analysis of the "unhappy consciousness" or the "beautiful soul". These themes have become part of the common culture and they are indeed often mentioned in the teachings at high schools and universities, but a reader of this Hegelian masterpiece is still lacking in French. Written by Hegel scholars, this book proceeds steps by step, reconstructing the various stages of the development of Hegel's thought in the Phenomenology of Spirit. Each contribution elaborates a synthetic commentary of a chapter or sub-chapter. The main objective is to help the reader understanding these chapters and their interconnections. But what is at stake is also to give a hint of the variety of philosophical discussions that have been triggered by them, and to invite the reader exploring all of its richness.